La parole reprise comme réparation conversationnelle dans le cadre de l'aphasie - Bonnans, Caroline; Delieutraz, Cannelle (My University, 2014)
Repairs are common to deal with problems in ordinary conversation and even more frequent when language and communication disorders disturb interaction. So, speech and language therapists who work with aphasic patients and their families are often faced with repairs. Referring to theory and clinical observations, we try to describe, analyze and understand this process, first in ordinary conversation and then in aphasic conversation. Finally, we describe how this mechanism can be used through two communication therapies.